Students' Perception on the Use of Google Classroom in Learning English: A Case Study at A State Islamic Secondary School - Widiyastuti, Nanik; Syarifudin, Syarifudin; Ariawan, Soni (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
The purpose of this study was to determine students' perceptions of online English learning during the covid-19 pandemic at State Islamic Secondary School (MTsN) 3 Mataram. This research is a descriptive research with a qualitative approach. Data was collected through a questionnaire which involved 40 students from class VIII-A. Based on the data analysis from questionnaire, it can be concluded that the students neutrally perceive the utilization of Google Classroom as they found several challenges such as absence of interaction room, lack of internet access etc. However, the interview results indicated that most of them have a positive perception on the use of Google Classroom during the COVID-19 pandemic due to ease of use, the flexibility and effectiveness as well as its access. It is suggested that teachers should be able to adjust their teaching strategy by considering students' factual condition as well as preferences.